Exploring the workload of informal caregiving in the context of HIV/NCD multimorbidity in South Africa. - Myrna van Pinxteren; Charlotte Slome; Frances S Mair; Carl R May; Naomi S Levitt (PLOS Global Public Health)
The importance of informal caregiving for chronic illness has been well established in African contexts but is underexplored in the context of HIV/NCD multimorbidity, particularly in South Africa. Building on treatment burden theories that investigate workload in the context of chronic illness, this paper explores how informal caregiving networks impact the capacity of people living with multimorbidity (PLWMM) in low-income settings in urban and rural South Africa. Qualitative semi-structured interviews were carried out with thirty people living with multimorbidity and sixteen informal caregivers between February and April 2021 in two settings, Cape Town (urban) and Bulungula (rural). Interviews were transcribed and data analysed both inductively and deductively using framework analysis, hereby, building on the principles of the burden of treatment theory (BoTT) as a theoretical lens. Our findings show that informal carers provided different types of support to people living with multimorbidity, including emotional, logistical, health services and informational support to ease the patient's treatment burden. Additional support networks, access to grants or financial security, and feeling a duty to care eased the perceived carer burden while a lack of social support, financial hardship and insufficient information decreased their capacity to support others. Overall, the availability of informal caregiving increases the self-management capacity of people living with multimorbidity in low-income settings in South Africa. Informal caregiving in the context of multimorbidity is structured through social obligations, kinship connections, cultural expectations, and an individual sense of agency. Carers, even when committed to assist, also experience caregiving opportunity costs, which are rarely addressed in the literature. By proposing interventions that can actively support informal caregivers, we can begin to develop solutions that can optimize the role of informal care networks, with a view to improve health-outcomes of PLWMM in South Africa.